Attitudes, Beliefs and Religious Practices of Workers in Pasto. An Exploratory Study - Ortega, Ximena Alexandra; Villamarín, Francisco Javier (Sociedad y Economía, 2012)
This article explores the attitudes, beliefs and religious practices of workers in the city of Pasto in 2009. The methodological strategy used to collect quantitative information on the exploration of the phenomenon considered is the review and classification secondary of social statistics. The data analyzed and interpreted in this article more than reveal an updated overview of the characteristics of the local religiosity from the information provided by the workers who participated in the study, raises new questions and questions that invite you to continue to open the paths of knowledge.